ANALISIS PENGENDALIAN INTERNAL ATAS PENGELOLAAN PERSEDIAAN MATERIAL PROYEK PADA DINAS BINA MARGA, CIPTA KARYA, DAN TATA RUANG KOTA MAKASSAR - Putri RM, Risma Febriyanti; Agustin, Hesti; Ilyas, Umrawati; Wahyuni, Sri; Sangka, Juandri (AT TARIIZ : Jurnal Ekonomi dan Bisnis Islam, 2025)
This study aims to describe and analyze the effectiveness of internal control in managing project material inventory at the Office of Public Works, Housing, and Spatial Planning of Makassar City. A qualitative descriptive approach was applied using structured interviews, field observations, and documentation, guided by the five COSO components: control environment, risk assessment, control activities, information and communication, and monitoring. Data were analyzed through reduction, presentation, and conclusion drawing to identify patterns, weaknesses, and supporting factors. The results indicate that internal control has been implemented through formal regulations, task distribution, authorization procedures, and routine monitoring. However, several weaknesses remain, including limited employee competence, reliance on manual recording, and suboptimal ethical and technical guidance. Overall, the internal control system is categorized as fairly good but requires strengthening through digital inventory recording, capacity building for human resources, and improved documentation to ensure more effective, accurate, and accountable material management.